A novel fabrication procedure for the preparation of polymethyl methacrylate lab-on-a-chip substrates - Narabhats Rannurags (2018)
Copyright © Taylor & Francis Group, LLC. Modification of a minicomputer numerical controller with a low cost diode laser for fabrication of polymethyl methacrylate chips has been demonstrated. The maximum power of the diode laser was 5 W at 808 nm. The scanning speed was 1.0-10.0 mm s-1 by the movement of x and y stages. The patterns of microchannels on the chip were designed using drawing software and then applied to software that controlled the operation of the controller. The parameters that affected the channel depth, width, and smoothness were studied by varying the laser power and speed of polymethyl methacrylate sheets with surface area of 4.0 × 6.0 cm2 and thickness of 0.1 cm. The optimum conditions were used to fabricate microchannels on each sheet giving different depths and widths over the range of 74 μm to 554 μm and 147 μm to 393 μm, respectively. The most appropriate conditions for polymethyl methacrylate chip fabrication were 5 W and 3 mm s-1 for the laser diode power and the speed, respectively. The optimal dimensions of the microchannel on the polymethyl methacrylate sheet were 226 μm in width and 202 μm in depth based on sensitivity, reproducibility, and low background signals. The microchannels were sealed with a polymethyl methacrylate cover plate by thermal bonding. The resulting chips were tested for iron(III) determination in water based on microreverse flow analysis.